De-risking solar auctions in sub-Saharan Africa – a comparison of site selection strategies in South Africa and Zambia - Kruger, W; Stritzke, S; Trotter, P (Elsevier, 2019)
While auctions are becoming increasingly popular for tendering renewable energy projects to private developers in Africa, their specific project risk implications are not yet fully understood. This paper identifies project risks arising from two types of auction schemes. It compares an approach where the government pre-selects the sites for future renewable energy plants in Zambia's Scaling Solar initiative to one where project developers choose, secure and conduct due diligence on their sites before bidding in South Africa's Africa's Renewable Energy Independent Power Producers Procurement Programme (REI4P). Semi-structured interviews with developers who have participated in both schemes reveal notably different risk profiles. Despite contrary intentions, site-specific risks have been perceived as the highest overall project risk in the government-led site selection process in Zambia. Specifically, site-specific risks were driven by several severe technical issues such as geotechnical, grid connection and solar irradiation uncertainties. In contrast, in South Africa's developer-led site selection process, site-specific risks have been reported to be important, but less pronounced, and more evenly distributed among technical, economic, legal, permitting and social risk factors. This paper recommends an auction design which minimises project risks for all stakeholders. Where governments pre-select sites, closely consulting the private sector is advisable prior to bidding to identify and mitigate technical and other site-specific risks.